2010
DOI: 10.1073/pnas.1015281107
|View full text |Cite
|
Sign up to set email alerts
|

Pigs and humans with cystic fibrosis have reduced insulin-like growth factor 1 (IGF1) levels at birth

Abstract: People with cystic fibrosis (CF) exhibit growth defects. That observation has been attributed, in part, to decreased insulin-like growth factor 1 (IGF1) levels, and the reduction has been blamed on malnutrition and pulmonary inflammation. However, patients with CF already have a reduced weight at birth, a manifestation not likely secondary to poor nutrition or inflammation. We found that, like humans, CF pigs were smaller than non-CF littermates and had lower IGF1 levels. To better understand the basis of IGF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(111 citation statements)
references
References 63 publications
5
102
2
2
Order By: Relevance
“…65 Our studies in newborn pigs revealed CFTR mRNA in the pituitary and hypothalamus and demonstrated that release of growth hormone is reduced in pituitary slice cultures isolated from CF pigs compared with non-CF littermates. 56 These studies are all consistent with a function of CFTR in modulating the neuroendocrine axis.…”
Section: Cftr Expression and Function In The Nervous Systemsupporting
confidence: 72%
See 1 more Smart Citation
“…65 Our studies in newborn pigs revealed CFTR mRNA in the pituitary and hypothalamus and demonstrated that release of growth hormone is reduced in pituitary slice cultures isolated from CF pigs compared with non-CF littermates. 56 These studies are all consistent with a function of CFTR in modulating the neuroendocrine axis.…”
Section: Cftr Expression and Function In The Nervous Systemsupporting
confidence: 72%
“…37 In pigs, CFTR is expressed in both the peripheral and central nervous systems. 55,56 In humans, CFTR has been identified in parvocellular ganglion, 57 hypothalamic neurons, 58 spinal cord neurons, 59 ganglion cells of the heart, 60 and sympathetic ganglion. 61 Both neuronal and glial cell CFTR expression has been reported in multiple species, 55,[62][63][64] with the exception of humans, in whom only neuronal CFTR has been reported.…”
Section: Cftr Expression and Function In The Nervous Systemmentioning
confidence: 99%
“…2A), similar to observations in CFTR −/− mice (24,28), CFTR −/− pigs (29), and humans with CF (30,31). These results suggest that the growth defect may not be due solely to reduced or absent CFTR in intestinal epithelium, a result consistent with findings in CF pigs and humans with CF (29).…”
Section: Resultssupporting
confidence: 80%
“…Porcine GH (pGH; AFP10864B) and anti-pGH antiserum (AFP5672099) were provided by Dr A. F. Parlow (National Hormone and Pituitary Program, Harbor-University of California-Los Angeles Medical Center, La Jolla, CA, USA). Plasma IGF-1 content was evaluated using a multispecies IGF-1 ELISA (Alpco Diagnostic, Salem, NH, USA), according to manufacturer's instructions, previously applied by Rogan et al (2010). The intra-and interassay coefficients of variation were 7.8% and 5.3%, respectively.…”
Section: Measurementsmentioning
confidence: 99%